Actin cytoskeleton aggregation involves the water channel protein aquaporin 1-mediated human chondrocyte degeneration: Aquaporin 1 links cytoskeleton to chondrocyte degeneration - Chen, Xiaoliang; Ma, Xiucai; Liu, Peng; Yang, Xiao; Yang, Yajun (Cellular and Molecular Biology, 2023)
Water metabolism and actin cytoskeleton remoulding act as essential characters in the process of osteoarthritis (OA). However, the relation between water channel protein aquaporin 1 (AQP1) and actin filament during chondrocytes (CHs) degeneration is not evident. Therefore, the present study aimed to evaluate the role of actin remoulding in the AQP1 mediated CHs degeneration. Primary CHs were collected from human hip cartilage and were degenerated from long-time monolayer culture or IL-1β stimulation. Besides, the CHs were transfected with AQP1‑specific siRNA or vectors to mediate the AQP1 gene expression. The potent inhibitor of actin polymerization Cytochalasin D was also supplemented during culture. RT-PCR was performed to determine the relative gene expression. AQP1 and F-actin fluorescence staining were performed to determine the AQP1 and F-actin organization. Moreover, the cell area and viability were also analyzed. AQP1 and F-actin organization were both increased during seven days’ CHs culture or three days’ IL-1β stimulation. Silencing of AQP1 prevented the cell area spreading and degenerated phenotype of CHs with suppression of F-actin aggregation in both natural or IL-1β-caused inflammatory-related degeneration. Besides, upregulating the AQP1 in the CHs via gene editing promoted the cell area spreading, and F-actin accumulation, and accelerated the CHs degeneration, which can be alleviated by Cytochalasin D treatment. These findings suggested that AQP1-mediated human CHs degeneration is related to F-actin aggregation.